6‐Shogaol exerts anti‐proliferative and pro‐apoptotic effects through the modulation of STAT3 and MAPKs signaling pathways. Issue 10 (24th June 2014) - Kim, Sung‐Moo; Kim, Chulwon; Bae, Hang; Lee, Jong Hyun; Baek, Seung Ho; Nam, Dongwoo; Chung, Won‐Seok; Shim, Bum Sang; Lee, Seok‐Geun; Kim, Sung‐Hoon; Sethi, Gautam; Ahn, Kwang Seok
Abstract : 6‐shogaol (6SG), one of active ingredients in ginger ( Zingiber officinale ), is known to exhibit anti‐proliferative, anti‐metastatic, and pro‐apoptotic activities through a mechanism that is not fully elucidated. Because the aberrant activation of STAT3 and MAPKs have been associated with regulation of proliferation, invasion, and metastasis of tumors, we hypothesized that 6SG modulates the activation of STAT3 and MAPKs activation in tumor cells. We found that 6SG strongly inhibited constitutive phosphorylation of STAT3 through inhibition of the activation of upstream JAK2 and c‐Src kinases and nuclear translocation of STAT3 on both MDA‐MB231 and DU145 cells. Also, 6SG caused the activation of JNK, p38 MAPK, and ERK. Inhibition of ROS generation by N‐acetylcysteine (NAC) significantly prevented 6SG‐induced apoptosis. 6SG induced apoptosis as characterized by cleavage of PARP, accumulation of cells in subG1 phase, positive Annexin V binding, down‐regulation of STAT3‐regulated proteins, and activation of caspase‐8, ‐9, ‐3 in both MDA‐MB231 cells. Compared with other analogues of 6SG, such as 6‐gingerol (6G), 8‐gingerol (8G), and 10‐gingerol (10G), 6SG was found to be the most potent blocker of STAT3 activation. We observed that the administration of 6SG alone significantly suppressed the growth of the tumor. As compared to the vehicle control, 6SG also suppressed the expression of STAT3‐regulated gene products such as Bcl‐2, Bcl‐xL, and Survivin in tumor tissues. Overall, these findings suggest that 6SG can interfere with multiple signaling cascades involved in tumorigenesis and can be used as a potential therapeutic candidate for both the prevention and treatment of cancer. © 2014 Wiley Periodicals, Inc.